Pengaruh Penghindaran Pajak Terhadap Pendanaan Eksternal Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - Pandapotan Ritonga (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2020)
Tax avoidance is an action taken by the company's financial manager to minimize the tax burden, of course this action poses a risk to the company including fines and loss of the company's good image in the public eye. In recent years, the tax authorities have been aggressive in distinguishing between tax evasion and tax evasion in tax planning efforts. The purpose of this study was to determine and analyze the effect of tax avoidance on external funding of manufacturing companies in the food and beverage sub-sector listed on the IDX. The method used in this research is quantitative associative with the sampling technique of purposive sampling method and the technique of collecting data by means of a documentation study, namely studying, classifying, and analyzing secondary data in the form of notes, financial reports, and other information as well as the analytical techniques used are simple linear regression. The results showed that there was no effect of tax avoidance on external funding.